Effects of Temperature on the Flexibility of Cow’s Skeletal Muscle on Silicone (S10) Plastination (Bangladesh Journal of Anatomy, 2020)
Context: Among many factors responsible for producing a good plastinate, temperature is one of the most important factors. The present study had been designed for making a suitable method of plastination of skeletal muscle in our country. Materials and Methods: This experimental study was carried out in Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of March, 2018 to February, 2019. Twenty (20) pieces of skeletal muscle were collected from approximately one-year-old slaughtered cow (Bos indicus) of government authorized slaughter house of Dhaka, Bangladesh which were designated as the ‘Cold Temperature group’ and the same numbers of pieces of skeletal muscle as the ‘Room Temperature group’. Then their percentage of changes in flexibility after every stages of plastination were measured and compared. Results: The percentage of changes in flexibility was non-significantly larger at cold temperature than at room temperature in fixation, dehydration and gas-curing stage. After gas-curing, the overall (from fresh stage to the end of plastination) the changes in flexibility is larger in Cold Temperature group than in Room Temperature group. Conclusions: In the present study, the percentage of change in flexibility of skeletal muscle shows better outcome at room temperature than at cold temperature, but this findings was statistically non significant. So, further researches with larger samples are recommended to reach a definitive conclusion.Bangladesh Journal of Anatomy January 2020, Vol. 18, No. 1, pp. 21-25